Combining ecosystem service value and landscape ecological risk to subdivide the riparian buffer zone of the Weihe River in Shaanxi - Yuyang Xie; Qiuchen Zhu; Hua Bai; Hongzhou He; Yuan Zhang (Ecological Indicators, 2024)
Riparian buffer zones are transitional and ecological intersections between land and water. These areas play a major role in advancing ecosystem protection and restoration. Here, we investigated the spatial and temporal evolution of land use, ecosystem service value (ESV), and landscape ecological risk (LER) in riparian buffer zones between 1990 and 2020 using the Shaanxi section of the Weihe River as a case study using a GIS grid, the unit-area-equivalent-factor method, the landscape ecological risk index, and the natural breakpoint method. We also established four ecological zones using standardized Z-scores. The predominant land categories in the study area comprised cultivated, construction, and grassland, which together accounted for more than 80 % of the total area. The construction land demonstrated the most significant increase of 4,062.33 hm2 area, and cultivated land showed most significant decrease of 13,048.56 hm2 area, between 1990 and 2020. Next, study-site ESV increased from 28.30 × 108 CNY in 1990 to 28.94 × 108 CNY in 2020, reflecting 2.26 % growth. High-value areas were principally bodies of water and primarily situated along the Weihe River, extending from west to east along the main channel. The LER of the study area was dominated by the lowest ecological risk, low ecological risk, and medium ecological risk classes, which collectively accounted for more than 70 % of the total area. The main land types in the areas with high ecological risk were forest land and cultivated land. The study area’s LER demonstrated a decreasing trend from 1990 to 2020, and the area with the lowest ecological risk and low ecological risk zones increased by 9.97 %. The riparian buffer zone was divided into ecological restoration, reconstruction, conservation, and protection zones based on two factors, namely, ESV and LER. The most dominant of these was the ecological reconstruction zone, which showed a 13.75 % decrease in area share between 1990 and 2020. The ecological restoration zone occupied the smallest area with the largest increase of 56.63 % during this period. In conclusion, this study contributes to ecological zoning and management of the riparian buffer zone along the main channel of the Weihe River. Appropriate zoning is integral to protecting this valuable ecosystem and achieving sustainable development of surrounding human communities.